2022
DOI: 10.3390/plants11192519
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Activities of Endemic Plants of the Australian Wet Tropics

Abstract: Plants have been a vital source of natural antioxidants since ancient times. Plants growing under various abiotic stress conditions often produce more defensive secondary metabolites such as phenolics, flavonoids, and terpenoids during adaptation to the environment. Many of these secondary metabolites are known to possess antioxidant and anti-inflammatory properties. This study tested seven plants sourced from the mountaintop areas (above 1000 m elevation) of Mount Lewis National Park (falls under the Wet Trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Using a modified literature method [ 29 , 30 , 31 ], the DPPH radical scavenging activity of each seagrass root and aerial extract was evaluated (performed in triplicate) by combining 100 μL of root and aerial extracts (and separated root or aerial extract for Z. muelleri ) at five different concentrations (500, 250, 125, 62.5, and 32.5 μg/mL in MeOH) with 200 μL of 0.1 mM DPPH (in MeOH). Absorbances were measured using a microplate reader (SPECTROstar ® Omega, BMG Labtech, Sydney, Australia) at 517 nm after 1 h of incubation in the dark condition at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Using a modified literature method [ 29 , 30 , 31 ], the DPPH radical scavenging activity of each seagrass root and aerial extract was evaluated (performed in triplicate) by combining 100 μL of root and aerial extracts (and separated root or aerial extract for Z. muelleri ) at five different concentrations (500, 250, 125, 62.5, and 32.5 μg/mL in MeOH) with 200 μL of 0.1 mM DPPH (in MeOH). Absorbances were measured using a microplate reader (SPECTROstar ® Omega, BMG Labtech, Sydney, Australia) at 517 nm after 1 h of incubation in the dark condition at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, monoterpenes, sesquiterpenes, and diterpenes were higher in young leaves than their mature leaves [ 3 , 4 ]. Recent studies conducted by Wangchuk’s group at James Cook identified the pharmaceutical potential of Australian Wet Tropics plants affected by climate change, and they have also discovered two novel drug lead molecules from one of the ecologically-directed tropical montane cloud forest plants [ 53 , 54 ]. Similarly, potent small molecules anti-inflammatory excretory-secretory products (ESP) derived from parasitic helminths were identified using metabolomics and lipidomics platforms [ 55 , 56 ].…”
Section: Approaches and Techniques For The Biodiscovery Of Anti-infla...mentioning
confidence: 99%
“…Studies have suggested that SMs, which function as plant defence mechanisms, possess intriguing pharmacological properties, including antioxidant and anti-inflammatory properties [178]. For instance, a novel galloyl-lawsoniaside A isolated from U. metrosideros leaf significantly suppressed pro-inflammatory cytokines, such as interferon-gamma and interleukins-17 (IL-17) and IL-18, and thus was identified as a new anti-inflammatory druglead molecule [132].…”
Section: Pharmacological Activities Of Isolated Phytochemicals Of Cli...mentioning
confidence: 99%
“…Osthol isolated from Leionema ellipticum also showed anti-inflammatory activity [143,146]. A study by Yeshi et al [178] analysed crude extracts from the leaves of seven plant species endemic to WTWHA of FNQ. Five of the seven plant species showed potent antioxidant and anti-inflammatory activities in in vitro human peripheral blood cells (PBMCs) assay [178].…”
Section: Pharmacological Activities Of Isolated Phytochemicals Of Cli...mentioning
confidence: 99%
See 1 more Smart Citation